Implementasi Kebijakan Parkir Berlangganan di Kabupaten Tuban - Faj'jrina, Faradila Sofia Nur; Wibawani, Sri (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Policy is a government activity aimed at providing positive impacts for the wider community. The success of a policy is determined not only by its formulation process but also by its implementation.The implementation of the subscription parking policy in Tuban Regency has shown quite effective results with the involvement of various stakeholders working together with the Tuban Regency Environmental and Transportation Agency, leading to an increase in parking fee revenue. Therefore, this study aims to further examine the implementation of the subscription parking policy in Tuban Regency.The research method used in this study is a qualitative descriptive method, analyzing based on Adam Smith's Implementation Model with several research focuses, including idealized policy, target groups, implementing organization, and environmental factors.The results of the study show that the focus on idealized policy has been effective, as evidenced by the interactions initiated by policy formulators such as the Environmental and Transportation Agency, the Regional Revenue Management Unit (UPT PPD), BPKPAD, the police, official parking attendants, and parking service users. The focus on target groups has been effectively achieved by raising public awareness and ensuring the safety and comfort of parking service users. However, the implementing organization was less effective due to insufficient attention to parking service users. The focus on environmental factors, influenced by cultural, social, economic, and political elements, supports the success of the subscription parking policy in Tuban Regency.